Modelo termoestrutural de um bloco de concreto da barragem de Itaipu a partir de dados de instrumentação e elementos finitos - Almeida, Alice Mioranza de (2021)
Among various measures to analyze the health and safety of concrete dams, temperature stands out, because dams, particularly those on buttresses, are strongly influenced by temperature fluctuations. This is due to thermal loads from solar radiation and variations in the temperature of the air, foundation and reservoir, which can cause deformations and develop cracks in the concrete. In this context, this work consists of a numerical computational modeling for the thermo-structural behavior of a block of buttresses of the Itaipu Hydroelectric Power Plant dam, in operation phase, using the Finite Element Method with the aid of Ansys® software. To achieve this purpose, the mathematical formulation of the computational thermo-structural model was presented, as well as the definition of the system boundary conditions with real instrumentation data. From the thermal modeling developed, the temperature field was obtained, and it approximates, with good precision, to the real temperature distribution experienced by the physical structure. In addition, the structural behavior of the block was well represented in most regions verified, and in the worst cases, it kept the mean absolute percentage error between instrumentation data and simulated data below 13,4%. Thus, the results obtained reveal the applicability of the computational tool used, due to its efficiency and ease of handling, in dam safety applications and preventive maintenance of the structure.